IDENTIFIKASI KUALITAS DAN TINGKAT PERSEBARAN INTRUSI AIR LAUT DI KECAMATAN ULAKAN TAPAKIS - Iska, Ridho; Edial, Helfia (DEPARTEMEN GEOGRAFI FIS UNP, 2026)
This study aims to determine the level of water quality physically (smell, color and taste) and chemically (pH, DHL, salinity, Fe, Mg, Na and hardness (CaCO3)) and the level and distribution of seawater intrusion in Ulakan Tapakis District. The research method used is descriptive quantitative, the research subject is a resident dug well where the research sample is determined using the Purposive Sampling technique with consideration of certain criteria according to needs, namely 7 samples of resident wells. The data analysis technique uses the storet method to determine the level of water quality and the scoring method is used to analyze the determination of the level of seawater intrusion and the overlay method to analyze the distribution of water quality and seawater intrusion. The results showed that (1) the level of water quality in Ulakan Tapakis Subdistrict physically dominant did not meet the water quality standard threshold requirements, (2) chemically did not meet the water quality standard threshold requirements because the Mg parameter exceeded the specified water quality standard threshold. with a value of 30mg/l. (3) The resident wells are known to have been polluted by seawater intrusion where the well in sample 6 is classified as brackish water with a DHL value of 1014µs/cm and a salinity of 6‰. Based on the conclusions, it can be concluded that: a) water quality is classified into class B (lightly polluted) and class C (moderately polluted). b) seawater intrusion is classified into class 1 (not intruded) and class 2 (light intrusion).